Interactive collaborative robotics : first International Conference, ICR 2016, Budapest, Hungary, August 24-26, 2016, Proceedings /: first International Conference, ICR 2016, Budapest, Hungary, August 24-26, 2016, Proceedings. (2016) - Unknown
No abstract available